P3_10 Red-shifted Speed Cameras - Worthy, Daniel; Garner, Robert; Gregory, Jenny; Taylor-Ashley, Jessica (Physics Special Topics, 2013)
This paper investigates whether a car could travel fast enough to be red-shifted out of a speed cameras range of vision. It also calculates the observed length contraction of such a car if it could go at this velocity. It was calculated that a car would need to travel at 0.178 times the speed of light to avoid being caught by the speed camera via the Doppler Eect. It was also calculate that a Ferrari 458 would contract by 7.3cm at this velocity.